2010
DOI: 10.1002/eji.200939998
|View full text |Cite
|
Sign up to set email alerts
|

Importance of TLR2 in the direct response of T lymphocytes to Schistosoma mansoni antigens

Abstract: The immunomodulatory effect of Schistosoma mansoni antigens has often been attributed to interaction with PRR expressed on APC. Our previous work has shown that S. mansonisoluble egg antigen (SEA) can induce, together with a Th2 response, TGF-b-dependent Foxp3 expression in naïve CD4 1 T cells from NOD mice. We found that SEA can directly upregulate the expression of surface-bound TGF-b in purified CD4 1 T cells in the absence of accessory cell interactions. In this study, we show that the C-type lectin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Schistosoma mansoni soluble egg antigen (SEA) directly act on CD4 þ T cells via TLR2 to induce the secretion of bioactive TGF-b [40]. P. falciparum extracts activate TGF-b receptor activation through membrane bound TGFb molecules and TGF-b dependent signals positively regulate TGF-b expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma mansoni soluble egg antigen (SEA) directly act on CD4 þ T cells via TLR2 to induce the secretion of bioactive TGF-b [40]. P. falciparum extracts activate TGF-b receptor activation through membrane bound TGFb molecules and TGF-b dependent signals positively regulate TGF-b expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Specific molecules including integrins and proteolytic enzymes provide various mechanisms to regulate TGF-b activation [21]. We have previously used LAP as an indicator of TGF-b on the cell surface of CD4 1 T cells [16,17]. x-1 enhances TGF-b secretion and RA converting enzyme expression in LPS-stimulated DCs…”
Section: Adapted To Generate Foxp3mentioning
confidence: 99%
“…This mode of action in diabetes prevention is similar to that found with helminth modulation of autoimmune disease, where effects are seen only at early time points. However, in the case of helminth infection, there is additional evidence of induction of Treg and invariant NK T (iNKT) cells to maintain an inhibition of diabetes prevention (5,15). It should also be noted that OdDHL does not mediate the profound diabetes prevention observed with helminth-derived products, which would be consistent with a lack of induction of robust immunoregulatory circuits by OdDHL.…”
Section: Discussionmentioning
confidence: 96%
“…Studies using animal models have demonstrated protection against autoimmune encephalomyelitis (EAE) and type 1 diabetes following some bacterial, viral, or helminth infections (3,6,7,14,25,27,30). It has also been demonstrated that a live infection may not be necessary for protection against type 1 diabetes, and parasite-derived products such as the soluble egg antigen (SEA) and soluble worm antigen (SWA) fractions of Schistosoma mansoni (5,29) as well as some bacterial components (1,17) can also be effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation